Barriers to transition care in inflammatory bowel disease: a survey of adult and paediatric gastroenterologists in the UK. (13th March 2011) - Sebastian, S; Jenkins, H; Arnott, I; Croft, N; Ahmad, T; McCartney, S; Russell, R K; Lindsay, J O
Abstract : Introduction: Preliminary data highlight the importance of appropriate transition for successful transfer of adolescents with IBD from paediatric to adult care. However, the ideal transition service has not been defined. The aim of this study was to identify both the perceived needs of adolescent IBD patients and the barriers to successful transition from the perspective of professionals involved in their care. Methods: A postal questionnaire was distributed to UK adult and paediatric gastroenterologists with an interest in IBD. The questionnaire utilised closed questions as well as ranked items on the importance of the various competencies of adolescents with IBD required for successful transition. The data is presented as mean scores±SD for aspects of the competencies. Results: The response rate for paediatric and adult gastroenterologists was 53.7% (71/132) and 49.3% (358/729) respectively (p=NS). A structured transition service was perceived as very important by 80.28% paediatric gastroenterologists compared to only 47.55 adult gastroenterologists (p=0.001). The suggested median age for initiation and completion of transition by both groups was 16 and 18 years respectively. A higher proportion of adult than paediatric gastroenterologists identified inadequacies in the preparation of adolescents for transfer 79.1% and 42.2% p=0.001). The main areas identified by adult gastroenterologists were patient lack of knowledge about the condition and treatment (35.4%) and co-ordination of care (40.1%) while paediatric gastroenterologists identified lack of self advocacy (30.9%) and co-ordination (29.5%). Lack of resources, clinical time and a critical mass of patients were the factors ranked highest by both paediatric and adult gastroenterologists as barriers to transition care. A significant proportion of adult (65.2%) and paediatric gastroenterologists (61.9%) highlighted suboptimal training for adult gastroenterologists in the care of adolescents and young adults with chronic diseases. Transition services appear to be more established in teaching hospital settings although there were marked regional differences. Conclusion: This survey highlights differences in the perception of adult and paediatric gastroenterologists in the management of transition care for adolescents with IBD. The perceived competencies that patients require also differed between the two groups of healthcare professionals. Lack of training and inadequate resources are the main barriers identified for development of a successful transition service. This survey provides data which may have implications in developing structured transition care services across the country.